2023
DOI: 10.1186/s12864-022-08990-y
|View full text |Cite
|
Sign up to set email alerts
|

A draft Diabrotica virgifera virgifera genome: insights into control and host plant adaption by a major maize pest insect

Abstract: Background Adaptations by arthropod pests to host plant defenses of crops determine their impacts on agricultural production. The larval host range of western corn rootworm, Diabrotica virgifera virgifera (Coleoptera: Chrysomelidae), is restricted to maize and a few grasses. Resistance of D. v. virgifera to crop rotation practices and multiple insecticides contributes to its status as the most damaging pest of cultivated maize in North America and Europe. The extent to which adaptations by this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 203 publications
(283 reference statements)
0
5
0
Order By: Relevance
“…2021 ), Diabrotica balteata 47% and 1.61 Gb ( King et al . 2023 ), Diabrotica virgifera 53% and 1.85 Gb ( Coates et al . 2023 ), and Altica viridicyanea 63% and 865 Mb ( Xue et al .…”
Section: Resultsmentioning
confidence: 99%
“…2021 ), Diabrotica balteata 47% and 1.61 Gb ( King et al . 2023 ), Diabrotica virgifera 53% and 1.85 Gb ( Coates et al . 2023 ), and Altica viridicyanea 63% and 865 Mb ( Xue et al .…”
Section: Resultsmentioning
confidence: 99%
“…For example, transcriptomic analysis was used to determine the mechanism of adaptation for the maize pest Diabrotica virgifera to different host plants. The study found that the larvae of this rootworm underwent fewer transcriptional changes when feeding on an alternate host plant than when feeding on a marginal or poor host (Coates et al 2023). Transcriptome pro ling of larvae of the weevil Pagiophloeus tsushimanus exposed to the plant-derived volatile compound linalool showed that linalool exposure induced the expression of genes encoding for P450s, cuticular proteins, antioxidases, heat shock proteins, and digestive enzymes ).…”
Section: Introductionmentioning
confidence: 87%
“…To perform phylogenomic analysis, the genome assemblies and gene annotations of thirteen Coleoptera insects and an outgroup D. melanogaster were retrieved from several public database, such as A. glabripennis (EnsemblMetazoa: Agla_1.0.48) 37 , Aethina tumida (NCBI RefSeq: GCF_024364675.1) 38 , Altica viridicyanea (NGDC GWH: GWHAMMQ00000000) 39 , Callosobruchus maculatus (NCBI GenBank: GCA_900659725.1) 40 , Dendroctonus ponderosae (NCBI GenBank: GCA_020466635.2) 41 , Dendroctonus valens 42 , Diabrotica virgifera (NCBI RefSeq: GCF_003013835.1) 43 , Gonioctena quinquepunctata (NCBI GenBank: GCA_018342105.1) 44 , Leptinotarsa decemlineata (i5k: OGSv1.2_GCF_000500325) 45 , Nebria riversi 46 , Photinus pyralis (NCBI RefSeq: GCF_008802855.1) 47 , Sitophilus oryzae (NCBI RefSeq: GCF_002938485.1) 48 , and Tribolium castaneum (EnsemblMetazoa: Tcas5.2.48) 49 . For each gene, only the longest transcript was kept for downstream analysis.…”
Section: Methodsmentioning
confidence: 99%